The commentary of al-Nayrizi on Books II-IV of Euclid's Elements of Geometry : with a translation of that portion of Book I missing from ms Leiden or. 399.1 but present in the newly discovered Qom manuscript edited by Rüdiger Arnzen - Anaritius, d. ca. 922. (Studies in Platonism, Neoplatonism, and the Platonic Tradition, 2009)
The Commentary of al-Nayrizi (circa 920) on Euclid's Elements of Geometry occupies an important place both in the history of mathematics and of philosophy, particularly Islamic philosophy. It is a compilation of original work by al-Nayrizi and of translations and commentaries made by others, such as Heron. It is the most influential Arabic mathematical manuscript in existence and a principle vehicle whereby mathematics was reborn in the Latin West. Furthermore, the Commentary on Euclid by the Platonic philosopher Simplicius, entirely reproduced by al-Nayrizi, and nowhere else extant, is essential to the study of the attempt to prove Euclid's Fifth Postulate from the preceding four. Al-Nayrizi was one of the two main sources from which Albertus Magnus (1193-1280), the Doctor Universalis, learned mathematics. This work presents an annotated English translation of Books II-IV and of a hitherto lost portion of Book I.